2019
DOI: 10.1103/physrevb.100.165201
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of defect band mechanism responsible for band gap evolution in (ZnO)1x(GaN)x alloys

Abstract: It is known that (ZnO) 1−x (GaN) x alloys demonstrate remarkable energy band bowing, making the material absorb in the visible range, in spite of the binary components being classical wide band gap semiconductors. However, the origin of this bowing is not settled; two major mechanisms are under debate: Influence of the orbital repulsion and/or formation of a defect band. In the present work, we applied a combination of the absorption and emission measurements on the samples exhibiting an outstanding nanoscale … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 47 publications
2
10
0
Order By: Relevance
“…As a point of comparison, VEELS experiments have been carried out on bulk (Ga 0.15 Zn 0.85 )(N 0.15 O 0.85 ) thin films synthesized by RF magnetron sputtering with a homogeneous composition. 13 Although the composition is similar to that of the (Ga 0.10 Zn 0.90 )(N 0.10 O 0.90 ) NCs described here, the VEELS spectra for those samples had a single onset at ∼2.5 eV, rather than two onsets, and showed a much wider variation in onsets (±0.25 eV). The significant qualitative difference in the VEELS spectra of the two types of (Ga 1−x Zn x )(N 1−x O x ) materials may be due to the core−shell-like nature of the NCs we describe here versus the homogeneous composition of the bulk (Ga 0.15 Zn 0.85 )(N 0.15 O 0.85 ).…”
Section: ■ Results and Discussionsupporting
confidence: 68%
“…As a point of comparison, VEELS experiments have been carried out on bulk (Ga 0.15 Zn 0.85 )(N 0.15 O 0.85 ) thin films synthesized by RF magnetron sputtering with a homogeneous composition. 13 Although the composition is similar to that of the (Ga 0.10 Zn 0.90 )(N 0.10 O 0.90 ) NCs described here, the VEELS spectra for those samples had a single onset at ∼2.5 eV, rather than two onsets, and showed a much wider variation in onsets (±0.25 eV). The significant qualitative difference in the VEELS spectra of the two types of (Ga 1−x Zn x )(N 1−x O x ) materials may be due to the core−shell-like nature of the NCs we describe here versus the homogeneous composition of the bulk (Ga 0.15 Zn 0.85 )(N 0.15 O 0.85 ).…”
Section: ■ Results and Discussionsupporting
confidence: 68%
“…This means that our previously shown bandgap measurements on the nanoscale with EELS-STEM, are the result of a homogeneous alloy and not an average of a mixture of phases. 18 Our findings support previous theoretical and experimental reports regarding the behaviour of N in ZnO. In particular, Fons et al 25 attributed the low p-type doping efficiency of N in ZnO to the low stability of N O , and showed the presence of N-N bonds by X-ray absorption experiments.…”
supporting
confidence: 91%
“…[9][10][11][12] Moreover, chemically induced phenomena such as phase separation and elemental clustering can play a detrimental role in the functional properties of an alloy system. Post-deposition annealing usually improves the crystalline quality [13][14][15][16] and recently Olsen et al 2,17,18 conducted a comprehensive study on magnetron sputtered ZnO-rich ZOGN thin films, elucidating the influence of composition and post-deposition annealing on the film properties, as well as investigating the mechanisms governing the band bowing effect. In the same study, 17 DFT calculations revealed that the total energy of the system decreased by increasing the amount of Ga-N bonds, predicting a re-arrangement of the nitrogen bonds during postdeposition annealing.…”
mentioning
confidence: 99%
“…Please do not adjust margins Please do not adjust margins Band-gap changes due to chemical disorder, also called bandbowing, have been observed in several other systems: ZnO-GaN, 18 (1-x)ZnGeN 2 2xGaN, 19 and Ni x Mg 1-x O. 20 In contrast, the atom disorder in the A(LiZn)S 2 phases is not inherited by a solid-solution and does not directly result in a composition dependent bandbowing.…”
Section: Please Do Not Adjust Marginsmentioning
confidence: 99%